Kehadiran Aplikasi Portal Perlindungan Konsumen di Sektor Jasa Keuangan - Kurniasih, Esy; Admiral, Admiral; Fudika, Moza Dela (JURNAL USM LAW REVIEW, 2024)
This study primarily aims to identify the consumer protection portal application based on POJK RI No. 31 /Pojk.07/2020 and, secondary, how the Financial Services Authority may settle consumer disputes and safeguard customers in the financial services industry. The need for this research is urgent since it is the first to address consumer protection in the financial services industry, consumer protection portal applications, and Financial Services Authority consumer dispute resolution. The normative juridical technique is the research methodology used in this study. The explanation above leads one to conclude that Law No. 21 of 2011 establishing the Financial Services Authority's mission is why the consumer protection portal application is available. In the financial services industry, disputes are settled either out-of-court or via the Financial Services Institution first if a settlement cannot be achieved. The recommendations state that, because APPK is still used generically, an upgrade to the system is required to maximize the application of legal protection through the principles of information openness and transparency.   Tujuan dari penelitian ini adalah untuk mempelajari bagaimana portal perlindungan konsumen digunakan sesuai dengan POJK RI No. 31 /Pojk.07/2020, dan bagaimana perlindungan konsumen di Sektor Jasa Keuangan dan Penyelesaian Sengketa Konsumen Oleh Otoritas Jasa Keuangan. Penelitian ini sangat penting karena penelitian sebelumnya belum membahas topik ini. Penelitian ini menggunakan yuridis normatif. Adapun kesimpulan dari diskusi di atas, undang-undang No. 21 tahun 2011 tentang Otoritas Jasa Keuangan memungkinkan portal perlindungan konsumen. Jika sengketa di sektor jasa keuangan tidak diselesaikan melalui Lembaga Jasa Keuangan, mereka akan dilanjutkan dengan penyelesaian di pengadilan atau di luar pengadilan. Rekomendasi mengenai praktik APPK masih banyak digunakan, dan sistem harus diperbarui untuk memaksimalkan penerapan perlindungan hukum melalui prinsip keterbukaan dan transparansi informasi.